Mechanisms of immune checkpoint inhibitor-mediated liver injury - Layla Shojaie; Myra Ali; Andrea Iorga; Lily Dara (Elsevier, 2021)
The immune checkpoints, cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) and programmed cell death protein-1/ligand-1 (PD-1/PD-L1) are vital contributors to immune regulation and tolerance. Recently immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy; however, they come with the cost of immune related adverse events involving multiple organs such as the liver. Due to its constant exposure to foreign antigens, the liver has evolved a high capacity for immune tolerance, therefore, blockade of the immune checkpoints can result in aberrant immune activation affecting the liver in up to 20% of patients depending on the agent(s) used and underlying factors. This type of hepatotoxicity is termed immune mediated liver injury from checkpoint inhibitors (ILICI) and is more common when CTLA4 and PD-1/PD-L1 are used in combination. The underlying mechanisms of this unique type of hepatotoxicity are not fully understood; however, the contribution of CD8+ cytotoxic T lymphocytes, various CD4+ T cells populations, cytokines, and the secondary activation of the innate immune system leading to liver injury have all been suggested. This review summarizes our current understanding of the underlying mechanisms of liver injury in immunotherapy using animal models of ILICI and available patient data from clinical studies.